Date recognition based on multi feature extraction - Min WANG; Jia WU; Shuo SUN; Sheng LI; Kang WANG (物联网学报)
Drug production date and expiration date are important indicators to measure the safety and effectiveness of drugs.The production date and validity period of liquid drugs in vertical bags are printed with numbers of 0～9.The recognition of the drug date of the hospital needs to meet the requirements of high speed and accuracy.The conventional template matching method and neural network recognition method have large amount of calculation and complex training.A drug date recognition method was proposed based on multi feature extraction.The combination of vertical line feature and three features for fine feature extraction of different digital characters has advantages of small amount of calculation and fast recognition speed.Compared with the recognition method of single extracted feature, it can effectively distinguish 10 different numbers, especially suitable for numbers of similar shape.It can provide patients with safe drug use guarantee, improve the management mode of the medical staff, improve the work efficiency, so as to improve the level of the pharmaceutical service of the hospital.